Peran media sosial dalam strategi public relation perbankan syariah - AZZAM, MUHAMMAD (Maliki Interdisciplinary Journal, 2025)
Islamic banking faces the challenge of increasing public awareness of their products and services. Social media is strategic in public relations because it allows direct interaction with customers, conveys Islamic values, and the benefits of mobile banking. Research shows that positive PR increases transactions through mobile banking, while social media influencers are not significant individually but contribute in a broader context. Social media provides a platform to respond to customer complaints in real time, increasing customer satisfaction. Islamic banks can promote products and services with consistent campaigns on Instagram, Facebook, and Twitter, attracting potential attention and strengthening existing loyalty. In addition, social media helps to hear customer feedback, build a positive image and public trust. Therefore, the role of social media in Islamic banking PR strategy is not only as a marketing tool, but a bridge of bank-society communication. Social media is important in Islamic banking PR for direct interaction, education, and reputation. Increasing mobile banking transactions and customer satisfaction, as well as building strong relationships with a wide audience. This study also helps in quick response to complaints and effective promotion of Islamic products.